Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.cll.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormones: relevance and measurement in the clinical laboratory

Abstract: The steroid hormones are synthesized in the adrenal cortex, the gonads, and the placenta; are all derived from cholesterol and many are of clinical importance. Steroid hormones are synthesized in the mitochondria and smooth endoplasmic reticulum. Because they are lipophilic, they cannot be stored in vesicles from which they would diffuse easily and are therefore synthesized when needed as precursors. Upon stimulation of the parent cell, steroid hormone precursors are converted to active hormones and diffuse ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(83 citation statements)
references
References 52 publications
0
62
0
9
Order By: Relevance
“…Immunoassay methods used in the present study have recently most often been replaced by LC/MS-MS, which compared with the immunoassay method, is a more efficient way of analyzing salivary hormones with higher specificity and sensitivity. However, previous studies on estradiol measurements, specifically, have shown a high correlation between MS and immunoassays of 0.969 (57).…”
Section: Discussionmentioning
confidence: 89%
“…Immunoassay methods used in the present study have recently most often been replaced by LC/MS-MS, which compared with the immunoassay method, is a more efficient way of analyzing salivary hormones with higher specificity and sensitivity. However, previous studies on estradiol measurements, specifically, have shown a high correlation between MS and immunoassays of 0.969 (57).…”
Section: Discussionmentioning
confidence: 89%
“…Steroid hormones are synthesized from cholesterol, and many are of great clinical importance (1). The measurement of steroid profiles indicates an important physiological state in endocrine systems, and it has been newly applied in the diagnoses and treatments of congenital adrenal hyperplasia, adrenal insufficiency, chronic pelvic pain and prostatitis, oncology (breast cancer) and athletic competition.…”
mentioning
confidence: 99%
“…Its messengers are hormones produced in glands and transported via the blood to the target cells [91,92]. This process can be disturbed at all levels of hypothalamus-pituitary gland-target organ regulation, so that hypoand hyper-functions may result.…”
Section: Steroid Hormonesmentioning
confidence: 99%